Etiologies and contributing factors of perinatal mortality: A report from southeast of Iran - Maryam Hadavi; Soghra Alidalaki; Maryam Abedininejad; Setare Akhavan (Elsevier, 2011)
Objective: The aim of this study was to investigate the etiology and risk factors of perinatal mortality in Rafsanjan, Iran. Materials and methods: This case-control prospective study was conducted on 321 perinatal deaths (as case group) and 321 live births who were alive until 28 days after birth (as control group) during a 2-year period. Data about demographic characteristics of mother, fetus, and newborn and also mother's obstetrics and clinical status was recorded in a questionnaire. Results: The most important causes of newborn death were prematurity (63.24%), cardiac arrest (11.49%), and septicemia (5.75%) as well as premature rupture of membrane, pregnancy-induced hypertension, placenta decolman, and congenital abnormality for stillbirth. A significant association was found among the fetal weight, gestational age, and amniotic fluid volume with stillbirth. Conclusion: Prematurity, cardiac arrest, and septicemia were the most important causes of neonatal mortality. It is concluded that attention to the following points is very important: adopting program for pregnancy care improvement, finding and removing risk factors of premature birth, control of infection in mother's and newborn's wards, examining of personnel skill about correct newborn resuscitation methods, and arrangement of training courses.